Fertility and the male life-cycle in the era of fertility decline - Bledsoe, Caroline; Lerner, Susana; Guyer, Jane (Oxford Oxford University Press, 2000)
This volume challenges the orthodox position on two of the main themes in fertility transition studies: the inevitable link between fewer children and quality of life and the focus on women as the sole important objects of study. In an era of unprecedented fertility decline, there is increasing concern about the lessening worldwide role that men play in the upbringing of children. The immense worldwide variation in the timing and sequencing of a man's life course events, the rise and fall in personal forunes, and the weight of society's hierarchies, all combine to affect the number of children a man fathers, when he fathers them, the number of partners he fathers them with, and the kind of support and recognition he bestows on them. The cross-disciplinary approach favoured here, including ethnographies, national surveys, and historical texts, avoids the narrow focus of many fertility studies texts. By providing detailed studies on a variety of countries ranging from Germany to Papua New Guinea, the contributors build an accurate picture of the global situation, while two Overview chapters give a wider perspective, and the Introduction synthesizes the themes identified and conclusions reached.
Keywords: Men Demographic transition; Fertility, Human; Male fertility trends in industrial countries